PENGARUH POLA ASUH PERMISIF DAN KOMPETENSI SOSIAL REMAJA TERHADAP PERILAKU EGOSENTRISME - Gracianing, Gabriella Yudhitia; Widodo, Bernardus (Educatio Vitae, 2015)
Egocentrism is a limited ability to interests or personal needs, not oriented to the separation / distinction between oneself and the people / other objects. In extreme teens are not concerned with other people's opinions of him. This thought is based on the hope that he will be the center of attention. This research aimed to analyze the effect of permissive parenting and adolescent social competence to egocentrism behavior. The population in this research are students class X SMKN 2 Jiwan Madiun learning activities 2014/2015 as much as 292 students with a sample 146 students. The sampling technique used is random sampling. Data obtained by using questionnaires shaped scale.. In this research, the authors propose three hypotheses namely: 1) The first minor hypothesis reads "if the intensity of permissive parenting is high, then the behavior of the higher egocentrism." 2) Minor second hypothesis states that "if the adolescent social competence is weak, then the higher the behavioral egocentrism" 3) Major hypothesis states that "if the intensity of high permissive parenting and adolescent social competence is low, then the higher the egosentrism behavior." Data analyzed by using multiple linear regression techniques regression line equation model Y = 30.384 + 0.221 - 0.021 further analysis of the results showed that: 1) there is influence between permissive parenting and egocentrism behavior t count=5.614 and t table=1.980, 2) there is the influence of social competence adolescents with behavioral egocentrism t count = -0.374 and t table = 1.980, 3) there is influence between permissive parenting and adolescent social competence with behavioral egocentrism F  count = 15.937 and F table=3.06. Based on these calculations can be summarized as follows: 1) t count > t table the first minor hypothesis is accepted, 2) t count < t table the second minor hypothesis is accepted, 3) F count > F table the major hypothesis is accepted.   Keywords: permissive parenting, adolescent social competence, behavioral egocentrism